2012
DOI: 10.1371/journal.pone.0043683
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of hMAPC and hMSC Transplantation after Stroke in Mice

Abstract: Stroke represents an attractive target for stem cell therapy. Although different types of cells have been employed in animal models, a direct comparison between cell sources has not been performed. The aim of our study was to assess the effect of human multipotent adult progenitor cells (hMAPCs) and human mesenchymal stem cells (hMSCs) on endogenous neurogenesis, angiogenesis and inflammation following stroke. BALB/Ca-RAG 2−/− γC−/− mice subjected to FeCl3 thrombosis mediated stroke were intracranially injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 56 publications
3
51
0
2
Order By: Relevance
“…These effects were then related, by different authors, with the expression of growth factors such as brain derived neurotrophic factor (BDNF), nerve growth factor (NGF), insulin growth factor 1 (IGF-1), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), fibroblast derived growth factor 2 (FGF-2), stem cells factor (SCF) and glial derived neurotrophic factor (GDNF), as reviewed by Teixeira et al [12]. Similar phenomena were also reported in vivo [13][14][15][16]. In fact, Munoz et al [13] reported that the injection of bone marrow MSCs (BM-MSCs) in the mice hippocampus led to an increased neuronal differentiation, mediated by neurotrophic factors.…”
Section: Introductionmentioning
confidence: 76%
“…These effects were then related, by different authors, with the expression of growth factors such as brain derived neurotrophic factor (BDNF), nerve growth factor (NGF), insulin growth factor 1 (IGF-1), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), fibroblast derived growth factor 2 (FGF-2), stem cells factor (SCF) and glial derived neurotrophic factor (GDNF), as reviewed by Teixeira et al [12]. Similar phenomena were also reported in vivo [13][14][15][16]. In fact, Munoz et al [13] reported that the injection of bone marrow MSCs (BM-MSCs) in the mice hippocampus led to an increased neuronal differentiation, mediated by neurotrophic factors.…”
Section: Introductionmentioning
confidence: 76%
“…Human MAPCs can be distinguished from human MSCs on the basis of cell surface phenotype, cell size, transcriptional profile, cytokine production, differentiation potential and replicative capacity (6, 10, 34, 35). Previous work showed that murine MAPCs exert therapeutic immunomodulatory effects in the context of graft-versus-host disease prophylaxis, in MLR systems in vitro, and that human MAPCs prevented inflammation in a murine model of stroke, supporting a role for these cells in treating human immune-mediated diseases (36)(37)(38).…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4][5] Due to their origin, bone marrow-derived stem cells are less debated from an ethical point of view than embryonic stem cells (ESCs). MSCs can differentiate into a number of mesenchymal phenotypes, including adipocytes, osteocytes, chondrocytes, and myocytes.…”
Section: Introductionmentioning
confidence: 99%